2004
DOI: 10.1103/physrevb.70.214526
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility ofCeMIn5andCe2MIn8

Abstract: The lattice parameters of the tetragonal compounds CeM In 5 and Ce 2 M In 8 (M =Rh, Ir and Co) have been studied as a function of pressure up to 15 GPa using a diamond anvil cell under both

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…we obtain B 0 = 81.1 ± 0.3 GPa and B 0 = 5.8 ± 0.1. Using the simple Murnaghan equation 33 results in the same fitted values for B 0 and B 0 within errors.These values are similar to those reported for other members of the Ce n M m In 3n+2m family 34. In these compounds, it was observed that adding MIn 2 layers stiffens the structure and increases the bulk modulus: B 0 = 67 GPa for CeIn3 , average B 0 = 70.4 GPa for Ce 2 MIn 8 (2 layers CeIn 3 + 1 layer MIn 2 ) and average B 0 = 81.4 GPa for CeMIn 5 (1 layer CeIn 3 + 1 layer MIn 2 ).…”
supporting
confidence: 89%
“…we obtain B 0 = 81.1 ± 0.3 GPa and B 0 = 5.8 ± 0.1. Using the simple Murnaghan equation 33 results in the same fitted values for B 0 and B 0 within errors.These values are similar to those reported for other members of the Ce n M m In 3n+2m family 34. In these compounds, it was observed that adding MIn 2 layers stiffens the structure and increases the bulk modulus: B 0 = 67 GPa for CeIn3 , average B 0 = 70.4 GPa for Ce 2 MIn 8 (2 layers CeIn 3 + 1 layer MIn 2 ) and average B 0 = 81.4 GPa for CeMIn 5 (1 layer CeIn 3 + 1 layer MIn 2 ).…”
supporting
confidence: 89%
“…The powder X-ray diffraction (XRD) patterns of both materials were indexed in the Fm3m (#225) space group, the typical cubic unit cell of PBAs. [ 33 ] Their structures were investigated by Rietveld refi nement ( Figure 3 ), [ 35 ] using compositions constrained by the chemical analysis and TGA measurements, i.e., 5% [Fe(CN) 6 ] n − vacancies, and 14.05 wt% water for 23-PBA or 4.86 wt% water for 07-PBA (Table S1, Supporting Information). The empty N site of the [Fe(CN) 6 ] n − vacancy is occupied by water, fulfi lling the octahedral environment of Fe.…”
Section: Materials Characterization-infl Uence Of Watermentioning
confidence: 99%
“…The crystal structure of PBA ( Figure 1 ) is similar to the ReO 3 and perovskite structure types, being comprised of cubes with TM residing on the corners and bridged by cyano groups along the edges, and thus generating a large central cavity (the A site in the perovskite structure). [ 33 ] Vacancies resulting from the absence of complete [TM′(CN) 6 ] 3−/4− units ( x in the above formula), are fi lled by water molecules with the O atoms occupying the empty sites, and coordinated to the adjacent TM. Water molecules can also be found within the central cavity (A site), either in the exact The major advantage of Mg batteries relies on their promise of employing an Mg metal negative electrode, which offers much higher energy density compared to graphitic carbon.…”
mentioning
confidence: 99%
“…A structural phase transition is simply expected as one possible cause for an anomaly in the P dependence of Q , but it is suggested from the x-ray diffraction measurements that no P-induced structural phase transition occurs up to 15 GPa in CeIrIn 5 [24]. We give an example of an anomaly in the P dependence of Q in CeCu 2 Si 2 relevant with the valence crossover.…”
mentioning
confidence: 93%